2003
DOI: 10.1097/00006324-200308000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Cycloplegic Autorefraction Results in Pre-School Children Using the Nikon Retinomax Plus and the Welch Allyn SureSight

Abstract: Even though the Retinomax Plus and the SureSight appear to agree with each other and with the results of cycloplegic retinoscopy for determining sphere and cylinder power, interpretation of the data should be considered as screening only because the actual magnitude of sphere and cylinder may vary from the actual magnitude. These results suggest that either device may be useful only as screening tools for assessing refractive error in pre-school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 9 publications
1
28
1
3
Order By: Relevance
“…We found good agreement for the Retinomax K-plus2 after cycloplegia that supports the results of earlier studies. 15,16,28,29 Several studies have compared agreement between the plusoptix and CR performed by an orthoptist or an ophthalmologist. 17,20,30 For reasons of cost-effectiveness, it would be preferable to screen large populations with lay screeners.…”
Section: Discussionmentioning
confidence: 99%
“…We found good agreement for the Retinomax K-plus2 after cycloplegia that supports the results of earlier studies. 15,16,28,29 Several studies have compared agreement between the plusoptix and CR performed by an orthoptist or an ophthalmologist. 17,20,30 For reasons of cost-effectiveness, it would be preferable to screen large populations with lay screeners.…”
Section: Discussionmentioning
confidence: 99%
“…Hand held autorefractors, which may be operated by lay persons, are expensive, but their reasonable accuracy makes them suitable for screening. 18 Kohler and Stigmar 13 concluded that a test for hyperopia could be safely omitted from a screening programme when +3D or less 59 35 5 6 12 5 5 1 .+3D 42 2 8 20 12 7 9 0 Total 101 37 13 26 24 12 14 1 *Refraction summed for both eyes. There is ample evidence, reinforced by the results of this study, that children with specific deviations of RE are better suited to certain tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Other new techniques of preschool vision screening include cycloplegic autorefraction (Retinomax Plus 127 ; Welch Allyn SureSight 127 ), noncycloplegic autorefraction (Retinomax 128 ), video autorefraction, 129 and wave-front analysis. 130 Other instruments for automated preschool vision screening are in further development and will increase in availability and usability in the future.…”
Section: Screening For Amblyopiamentioning
confidence: 99%